If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 3 = 2x + 31 Reorder the terms: 3 + 6x = 2x + 31 Reorder the terms: 3 + 6x = 31 + 2x Solving 3 + 6x = 31 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 3 + 6x + -2x = 31 + 2x + -2x Combine like terms: 6x + -2x = 4x 3 + 4x = 31 + 2x + -2x Combine like terms: 2x + -2x = 0 3 + 4x = 31 + 0 3 + 4x = 31 Add '-3' to each side of the equation. 3 + -3 + 4x = 31 + -3 Combine like terms: 3 + -3 = 0 0 + 4x = 31 + -3 4x = 31 + -3 Combine like terms: 31 + -3 = 28 4x = 28 Divide each side by '4'. x = 7 Simplifying x = 7
| m-14.6=9.74 | | 4+2x=5x-2 | | w-8=32 | | 4y-8=5y-1 | | 17dl=l | | 3x+4=-36-5x | | x=2*8+77 | | 16+5x= | | 3x+4=-35-5x | | (2x+5)x(7x-2)=(4x+3)x(5x-1)+82 | | 4(d-7)=524 | | X-4X+3Y+9Y-12=0 | | 5x+3x+120=360 | | 6*x*y-12=0 | | x+3x-4= | | f(x)=2x^4-3x | | y-1=-6/7(14) | | 3(2x+3)=45 | | (2x+5)=27 | | (x-5)10+(1-2x)15=(3-x)14 | | x-12y=-36 | | 80-6x=7x+16 | | 7(9)+9y=63 | | 3y-5x=0 | | 3y+2(-3)=-6 | | (8x-8)/7-4(x+4)/7+7=8 | | x^2-24x-51=0 | | x^3-24x^2-51x=0 | | 15x+12y=13 | | 3x+33=11x-66 | | 1/5t-3=17 | | 9y-9y= |